The Correlation Between Students' Anxiety (Cognitive, Affective, Behavior) and Speaking Performance - Fahira Pramudya Sari; Yuri Lolita (JALL (Journal of Applied Linguistics and Literacy), 2023)
The aims of this study is to find out (1) the correlation between students’ anxiety and their speaking performance, (2) what extent do the students feel anxious on English speaking performance. This research conducted in Vocational High School especially in tenth grade with the total 65 students as participants. Quantitative method was conducted in this research. Questionnaire and students’ speaking performance score were used as instruments. The result indicated there was negative correlation in medium correlation criteria between students’ anxiety and speaking performance. The component that more contribute to the students’ speaking performance is the affective component. It can be inferred from the outcome that anxiety can affect their score in speaking performance score, especially the students’ affective.